Hyaluronan and the importance of hyaluronan in diagnosis and treatment - Aytekin, Metin; Caylak, Emrah (Turkish Assoc Tuberculosis & Thorax, 2009)
Hyaluronan is a glycosylaminoglycan and is the main component of the extracellular matrix. It was first described in 1934 and has many structural and physiological functions in the human body. An upcoming area of study relates to the hyaluronan receptors, since these affect the metabolism and function of hyaluronan. This knowledge will be useful in evaluating the role of hyaluronan in diseases, as a therapeutic agent for inflammation disorders and as a diagnostic biomarker. In this review, we discussed the structure of hyaluronan and its role in diseases.
Hiyalüronan, tani ve tedavideki önemi
Keywords: Hyaluronan; metabolism; pathology; treatment; diagnosis